Effects of activation of an alcohol metabolic gene, cigarette smoking, and alcohol intake on the incidence of metachronous gastric cancer in patients who underwent endoscopic resection for gastric cancer: A multicenter retrospective pilot study. Issue 4 (31st March 2023) - Abiko, Satoshi; Shimizu, Yuichi; Ishikawa, Marin; Inoue, Masaki; Nakajima, Katsuma; Kohya, Risako; Hirata, Koji; Suzuki, Kazuharu; Sugiura, Ryo; Miyamoto, Shuichi; Kinoshita, Kenji; Hatanaka, Kazuteru; et al.
Abstract: Background and Aim: Metachronous gastric cancer (GC) frequently occurs in patients who have undergone endoscopic resection (ER) for GC. We evaluated the risk for development of metachronous GC following ER for GC based on genetic polymorphisms for alcohol dehydrogenase‐1B (ADH1B) and aldehyde dehydrogenase‐2 (ALDH2), as well as alcohol consumption and smoking habits. Methods: We studied 77 patients who underwent ER for GC (median follow‐up of 84 months). Genotyping of ADH1B/ALDH2 was performed using saliva sampling. Histories of alcohol consumption and smoking before and after ER and Helicobacter pylori eradication were documented. Results: Multivariate analyses revealed that homozygous slow‐metabolizing ADH1B (hazard ratio [HR] = 2.38, P < 0.13), heavy smoking (HR = 2.36, P < 0.09), and cigarette smoking after ER (HR = 2.47, P < 0.10) were not independently associated with the risk of secondary GC development. We analyzed the cessation status of the 38 patients who were classified as heavy smokers before ER based on their smoking habits after the ER and divided them into a cessation group ( n = 27, non‐smokers after ER) and a non‐cessation group ( n = 11). Cumulative incidence curves of secondary GC in the cessation and non‐cessation groups revealed 5‐year incidence rates of 19.0% and 45.0%, respectively ( P = 0.02). Conclusion: Continued cigarette smoking, at a high level, may be an important risk factor for the development of metachronous GC. Advice for smoking cessation should be given. Abstract : We evaluated the risk for development of metachronous GC following ER for GC based on genetic polymorphisms for alcohol dehydrogenase‐1B (ADH1B) and aldehyde dehydrogenase‐2 (ALDH2), as well as alcohol consumption and smoking habits. Continued cigarette smoking, at a high level, may be an important risk factor for the development of metachronous GC. Advice for smoking cessation should be given.